ANALISIS NILAI TAMBAH PISANG â€œGOROHOâ€ (Musa acuminafe, sp) (STUDI KASUS: SABUAH UNGU PANTAI MALALAYANG KOTA MANADO) - Velly Maria Karamoy; Agnes E. Loho; Tommy F. Lolowang (AGRI-SOSIOEKONOMI, 2017)
This study aims to find out how much added value goroho bananas. This research was carried out for 3 months in Sabuah Purple Malalayang Beach at Manado City. This research uses primary data with direct interview technique to the manager. The results showed that from the four forms of processed banana goroho goroho banana flour sticks, regular sticks, chips, and split four; The most value added in the form of processed banana goroho flour sticks with a value of IDR 2816.78 compared with other processed forms such as common sticks IDR 1567,97, chips IDR 1091,78, and split four IDR 1176,78.